PRAKSIS HUKUM PIDANA DALAM PERLINDUNGAN KONSUMEN - Putra, Danil (IAIN Langsa, 2019)
This paper discusses the issue of consumer protection in criminal law, where in the applicable laws and regulations, the inclusion of standard clauses in motor vehicle loan agreements through leasing institutions whose contents are detrimental to consumers has been explicitly prohibited, even in the Consumer Protection Act there is a criminal threat for business actors who violate these provisions. But in practice, motor vehicle financing agreements through leasing still include standard clauses that provide flexibility to act for creditors when there is a problem in installment payments. With law enforcement against violating business actors, it is expected to provide a deterrent effect for business actors.